Exceptional twin buildings of type C2 : a contribution to the classification of twin buildings - Wendlandt, Katharina; Justus Liebig University Giessen (My University, 2020)
We provide a classification of affine twin buildings of type C2tilde having at least one exceptional residue with one exception in the case E7 in characteristic 2. Relying on the main results of [TW], [W09] and [MPW] we settle the uniqueness. The existence part is settled by refining and adapting the theory of descent in buildings developed in [MPW] to our specific situation.

Wir klassifizieren diejenigen affinen Zwillingsgebäude vom Typ C2, die mindestens ein Residuum vom Ausnahmetyp enthalten. Ein noch offenes Problem bildet der Spezialfall E7 in Charakteristik zwei. Die Eindeutigkeit basiert auf den Hauptresultaten in [TW], [W09] und [MPW]. Der Existenzbeweis beruht auf einer Weiterentwicklung der Theorie über descent in buildings in [MPW].
C2-Zwillingsgebäude vom Ausnahmetyp
Keywords: ddc:510